Attitude of intern doctors and B.Sc. nursing students regarding various aspects of biomedical waste (management and handling) rules: a cross sectional study - Acharya, Rekha; Sharma, Gaurav; Sethia, Renu; Meena, Ratti Ram (International Journal Of Community Medicine And Public Health, 2017)
Background: Different types of waste are generated during healthcare activities. The waste so generated has chance of causing serious infection and also injury to persons who come in contact with it whether the contact is direct or indirect. Safe and sustainable health care waste management is not possible without a favourable attitude among health care providers. The objective of the study was to assess the attitude of Intern doctors and B.Sc. nursing students: the future health care providers, regarding various aspects of Biomedical Waste (Management and handling) Rules. Methods: This was a cross-sectional study. The study was conducted amongst Intern doctors and B.Sc. nursing students posted at Prince Bijay Singh Memorial (PBM) and associated group of hospitals attached to Sardar Patel Medical College, Bikaner. Results: In the study out of 204 respondents, 54.4% were B.Sc. nursing students and 45.6% were intern doctors. Statistically significant difference was seen in overall attitude of study population belonging to different professional group regarding biomedical waste management. Overall the attitude of study group was favourable. Conclusions: Favourable attitude of health care workers will go a long way in better implementation of biomedical waste management rules and thereby help in decreasing adverse health effects of improper waste handling.